The Virtual Trojan Horse in Modern Conflicts - Al-Aridi, Alaa (Teisė, 2018)
The article will examine the applicability of international laws to cyber affairs by focusing on cyber-attacks that fall under the jus ad bellum the law relating resort to the use of force in the cyber field; and analyzing the applicability of article 2/4 of the UN charter as well the right to self-defense articulated in article 51 of the UN charter; on the other hand will analyze how the legal parameters of IHL (jus in bello) apply to cyber operations in armed conflicts.
Keywords: none